A Needs Analysis for Developing an SDG 11 Integrated Reading Media to Support Reading Engagement in Kindergarten - Indah Amaliya; Putu Kerti Nitiasih; Ni Wayan Monik Rismadewi (Yayasan Zia Salsabila, 2026)
Low reading engagement can affect the quality of young children’s literacy experiences. Although literacy activities have been implemented in kindergarten classrooms, limitations in reading media and the lack of contextual learning materials remain challenges in sustaining children’s attention and participation during reading activities. This study aimed to analyze teachers’ and students’ needs regarding the development of SDG 11 integrated reading media to support reading engagement in kindergarten. The study employed a qualitative descriptive design and was conducted in Class B1 at Undiksha Kindergarten Lab School. Data were collected through classroom observations and semi-structured interviews with the English teacher and were analyzed using thematic analysis. The findings revealed that students showed interest at the beginning of reading activities, however, their engagement, attention, and participation tended to decline as the activities progressed. The limited availability and variety of reading materials, the small size of existing storybooks, and difficulties in understanding unfamiliar vocabulary were identified as factors influencing students’ reading engagement. The findings also showed that shared reading activities were conducted but had not yet been implemented regularly, while reading materials integrating SDG 11 themes were not available in the classroom. Furthermore, the teacher expressed the need for visually appealing, interactive, and developmentally appropriate reading media to support literacy learning. These findings indicate the need to develop SDG 11 integrated reading media that can support shared reading activities, enhance reading engagement, and introduce sustainable cities and communities concepts to young children.